Recovery Method and Parameter Optimization of a Pilot Test for Conformance Control Flooding and Thermal Recovery in the Offshore Heavy Oilfield - Yanxia Zhou; Xiangguo Lu; Bao Cao; Yigang Liu; Yunbao Zhang; Xun Zhong (Geofluids)
NB35-2 oilfield is a typical offshore sandstone reservoir with viscous crude oil and high permeability. Due to the inherent severe heterogeneity, the efficiency of conventional water flooding is pretty low and usually accompanied with early water breakthrough. In order to recover the residual oil and better realize its potential, applications of enhanced oil recovery (EOR) technology are necessary. However, the selection of EOR method and related parameters may directly impact the final results and can be noticeably different for different reservoirs; therefore, to optimize the oil production rate and final oil recovery, systematical optimization of every detail based on the condition of a specific reservoir is of key importance. In this paper, physical simulations were first conducted to select the best recovery methods for the target area based on the static geophysical model under the guidance of reservoir engineering theory. Then, detailed development variants for each method were determined by numerical simulation with the support of data obtained from previous pilot tests (polymer gel flooding and thermal fluid huff and puff) conducted in this area. Three exploitation methods were developed for the target well group, including polymer gel flooding (conformance control, Pattern 1), steam huff and puff (thermal recovery method, Pattern 2), and a combination of polymer gel flooding and steam huff and puff (conformance control and thermal recovery, Pattern 3). The numerical simulation result also showed that Pattern 3 yielded the highest oil recovery. Moreover, the amount of additional oil being recovered by applying Pattern 3 was even higher than the total additional oil being extracted by Patterns 1 and 2. In addition, sensitivity analysis was conducted to rank the most important parameters based on the three Patterns. At last, it is thought that the synergistic effect between conformance control and thermal recovery made more oil recovered, which was intuitively clarified in the mechanism analysis.